Fe-based alloy powder and method for manufacturing additive manufactured body
By using Fe-based alloy powder with a carbon equivalent Ceq of less than 0.95 mass% and controlling the Ms point, the problem of cracks in the additive manufacturing body is solved and a balance between high thermal conductivity and hardness is achieved.
Patent Information
- Application Number
- CN202380043298.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-12
- Filing Date
- 2023-09-11
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art has failed to effectively suppress cracks in the additive manufacturing body while improving the thermal conductivity and hardness of the additive manufacturing body.
By using Fe-based alloy powder with a carbon equivalent Ceq of 0.95 mass% or less and controlling the Ms point in the range of 340 to 385°C during the manufacturing process, cracks in the additively manufactured body can be suppressed.
It effectively suppresses cracks in the additive manufacturing body while ensuring high thermal conductivity and hardness of the additive manufacturing body.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The present invention relates to Fe-based alloy powder for use in additively manufactured products, and a method for manufacturing an additively manufactured product using the Fe-based alloy powder. Background Art
[0002] Various Fe-based alloy powders for use in additive manufacturing and the like to produce additively manufactured products and additively manufactured products obtained using the same have been proposed.
[0003] Patent Document 1 (Japanese Patent No. 7108014) discloses an average particle size D 50 The invention discloses an Fe-based alloy powder with a diameter of 200 μm or less, which contains, by mass%, 0.40<C<0.70, Si<0.60, Mn<0.90, Cr<4.00, Ni<2.00, 0.90<Mo<1.20, W<2.00, V<0.60, 0.01≤Al<0.10, and the balance is composed of Fe and unavoidable impurities, and it is recorded that the quenching and tempering hardness related index K1 is greater than 21.7, and the thermal conductivity related index K2 is greater than 29.0. By using the Fe-based alloy powder to manufacture an additively manufactured body, the thermal conductivity and hardness of the additively manufactured body are improved.
[0004] Patent document 2 (Japanese Patent Publication No. 2022-092524) discloses that an additively manufactured body made of Fe-based alloy powder has a thermal conductivity-related index T1 greater than 32.0, a softening resistance-related index T2 greater than 50.0, and an average size PC of carbides contained in the additively manufactured body less than 3.0 [μm]. Thus, both high thermal conductivity and high hardness of the additively manufactured body are achieved.
[0005] Patent document 3 (Japanese Patent Publication No. 2021-181591) discloses a metal powder, which contains, by mass%, 0.1≤C≤0.4, 0.005≤Si≤1.5, 0.3≤Mn≤8.0, 2.0≤Cr≤15.0, 2.0≤Ni≤10.0, 0.1≤Mo≤3.0, 0.1≤V≤2.0, 0.010≤N≤0.200, and 0.01≤Al≤4.0, and the balance is composed of Fe and unavoidable impurities, and the variable A (A=15C+Mn+0.5Cr+Ni) related to the Ms point is recorded, satisfying the relationship of "10<A<20". As a result, when an additive manufacturing body is manufactured from the metal powder, an additive manufacturing body with less cracks and warpage, moderate hardness and high thermal conductivity is obtained.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent No. 7108014
[0009] Patent Document 2: Japanese Patent Application Publication No. 2022-092524
[0010] Patent Document 3: Japanese Patent Application Publication No. 2021-181591 Summary of the invention
[0011] In Patent Documents 1 and 2, although the thermal conductivity and hardness of the additively manufactured body are improved, no attention is paid to the cracks of the additively manufactured body. On the other hand, in Patent Document 3, by satisfying "10<A<20", an additively manufactured body with less cracks and strain is obtained. However, in Comparative Example 5 described in Patent Document 3, although "10<A<20" is not satisfied, no cracks occur, so variable A is not suitable as a parameter for evaluating cracks in additively manufactured bodies.
[0012] The present inventors focused on the carbon equivalent Ceq described later in Fe-based alloy powders having a predetermined chemical composition, and found that cracks in additively manufactured products can be suppressed by using Fe-based alloy powders whose parameters satisfy predetermined conditions, thereby completing the present invention.
[0013] According to the present invention, the following aspects are provided.
[0014] [Method 1]
[0015] An Fe-based alloy powder, containing, by mass %,
[0016] 0.30≤C≤0.50
[0017] 0<Si≤0.40
[0018] 0<Mn≤0.40
[0019] 0.85≤Cr≤1.75
[0020] 0<Ni≤0.40
[0021] 0.70≤Mo≤1.20
[0022] 0<V≤0.60
[0023] 0<Al≤0.10
[0024] 0≤W≤0.40%,
[0025] The balance contains Fe and unavoidable impurities, among which,
[0026] Among the elements contained in the Fe-based alloy powder, a carbon equivalent Ceq in which influence of elements other than carbon is converted into a carbon amount is 0.95 mass % or less.
[0027] [Method 2]
[0028] The Fe-based alloy powder according to aspect 1 has an Ms point of 340 to 385°C.
[0029] [Method 3]
[0030] The Fe-based alloy powder according to aspect 1 or 2, wherein W is contained in an amount higher than 0% and not more than 0.40 mass %.
[0031] [Method 4]
[0032] The Fe-based alloy powder according to any one of aspects 1 to 3, wherein an index K1 represented by the following formula is 17.00 mass % or more:
[0033] [Formula 1]
[0034]
[0035] Furthermore, the index K2 represented by the following formula is 44.00 mass % or more.
[0036] [Formula 2]
[0037]
[0038] [Method 5]
[0039] A method for producing an additively manufactured object, comprising irradiating an Fe-based alloy powder according to any one of the first to fourth aspects with an energy beam to melt and solidify the powder, thereby producing the additively manufactured object.
[0040] By producing an additively manufactured product using the Fe-based alloy powder of the present invention, cracks in the additively manufactured product can be suppressed. DETAILED DESCRIPTION
[0041] (Manufacturing method of additively manufactured body)
[0042] The Fe-based alloy powder of the present embodiment is used for the manufacture of additively manufactured bodies. In the manufacture of additively manufactured bodies, after preparing the Fe-based alloy powder, the Fe-based alloy powder is melted and solidified to obtain an additively manufactured body that has not been heat treated. As a process for melting and solidifying the Fe-based alloy powder, a rapid melting and rapid cooling solidification process can be cited. As specific examples of this process, a three-dimensional additive manufacturing method, a thermal spraying method, a laser cladding method, and a surfacing method can be cited. In particular, a three-dimensional additive manufacturing method using a powder bed method can be preferably used.
[0043] In the three-dimensional additive manufacturing method of the powder bed method, a 3D printer is used to irradiate the laid Fe-based alloy powder with an energy beam such as a laser beam or an electron beam, thereby rapidly heating the Fe-based alloy powder and melting it. Thereafter, the Fe-based alloy powder is rapidly solidified. Through this melting and solidification, the Fe-based alloy powders are bonded to each other. The energy beam is selectively irradiated to a portion of the Fe-based alloy powder. In addition, the portion of the Fe-based alloy powder that is not irradiated with the energy beam does not melt, and a bonding layer is formed only on the portion that is irradiated with the energy beam.
[0044] By laying Fe-based alloy powder on this bonding layer and irradiating it with an energy beam, the above-mentioned melting and solidification occur, thereby forming a new bonding layer. By repeating such a process, the aggregate of the bonding layer can be gradually grown to manufacture an additively manufactured body with a desired three-dimensional shape. By utilizing the three-dimensional additive manufacturing method, it is easy to manufacture additively manufactured bodies with complex shapes.
[0045] (Fe-based alloy powder)
[0046] The Fe-based alloy powder contains C, Si, Mn, Cr, Ni, Mo, V and Al, and the balance contains Fe and inevitable impurities. Here, the content (mass %) of each of C, Si, Mn, Cr, Ni, Mo, V and Al satisfies the conditions shown in the following formulas (1) to (8). In the following formulas (2), (3), (5), (7) and (8), since each element is an essential element contained in the Fe-based alloy powder, although there is no specific lower limit value, it should be understood that the content of each element is higher than 0 mass %.
[0047] 0.30≤C≤0.50 …(1)
[0048] Si≤0.40 …(2)
[0049] Mn≤0.40 …(3)
[0050] 0.85≤Cr≤1.75 …(4)
[0051] Ni≤0.40 …(5)
[0052] 0.70≤Mo≤1.20 …(6)
[0053] V≤0.60 …(7)
[0054] Al≤0.10 …(8)
[0055] The Fe-based alloy powder may contain W. That is, W is an arbitrary element. The content of W may be 0.40 mass % or less.
[0056] In the Fe-based alloy powder, the carbon equivalent Ceq satisfies the condition represented by the following formula (9). In addition, it is preferable that the Ms point satisfies the condition represented by the following formula (10).
[0057] Ceq≤0.95 … (9)
[0058] 340≤Ms≤385 … (10)
[0059] The carbon equivalent Ceq is a value (mass %) obtained by converting the influence of elements other than carbon in the Fe-based alloy powder into the carbon amount. It is represented by the following formula (11). In addition, the Ms point is the temperature at which martensite begins to form during quenching cooling (i.e., the temperature at which steel begins to harden) (°C), which is represented by the following formula (12). Although the Ms point can also be experimentally determined by a Formastor test, the Ms point in this embodiment is not a value obtained by experiment, but a value obtained by substituting the content of each element into the following formula (12).
[0060] [Formula 3]
[0061]
[0062] In the above formula (11), C, Si, Mn, Cr, Ni, Mo, W, and V are the contents (mass %) of the respective elements in the Fe-based alloy powder. In the above formula (12), C, Mn, V, Ni, Cr, Mo, W, Co, and Al are the contents (mass %) of the respective elements in the Fe-based alloy powder. In addition, since Co is not contained in the Fe-based alloy powder of the present invention, the content of Co in the above formula (12) is 0 mass %.
[0063] As shown in the above formula (9), by making the carbon equivalent Ceq less than 0.95 mass%, the hardness of the additively manufactured body after modeling can be prevented from becoming too high, and the toughness of the additively manufactured body during modeling can be ensured. If the hardness of the additively manufactured body is too high, cracks will occur in the additively manufactured body during modeling. Therefore, by ensuring the toughness of the additively manufactured body, the occurrence of cracks in the additively manufactured body can be suppressed. The carbon equivalent Ceq is preferably less than 0.91 mass%. The lower limit of the carbon equivalent Ceq is not particularly limited, but is usually greater than 0.75 mass%, and more typically greater than 0.80 mass%.
[0064] As shown in the above formula (10), by making the Ms point above 340°C, the amount of retained austenite contained in the additively manufactured body can be reduced. When the Ms point is lower than 340°C, retained austenite is likely to occur, and as the retained austenite gradually transforms into martensite, the internal stress increases, and cracks (i.e., season cracking) are likely to occur. Preferably, the Ms point is above 345°C.
[0065] In addition, as shown in the above formula (10), by making the Ms point below 385°C, it is possible to ensure a moderate amount of retained austenite, while relieving the thermal stress during molding and suppressing cracks in the additively manufactured body. As mentioned above, if the retained austenite exists excessively, seasonal cracks are likely to occur, but by making the retained austenite exist in a moderate amount, the highly ductile retained austenite can relieve the thermal stress during molding and suppress cracks in the additively manufactured body. The Ms point is preferably below 370°C, and more preferably below 360°C.
[0066] (C content)
[0067] C is an essential element that strengthens the matrix by solid solution and forms carbides to promote precipitation. In the case of die steel formed by the conventional forging method, there is a problem that an increase in carbon content promotes microsegregation, but in the additive manufacturing process, because fine carbides are obtained by rapid cooling, more carbon can be contained compared to forged materials, thereby improving the hardness of the additively manufactured body.
[0068] By making the C content 0.30 mass % or more, sufficient quenching and tempering hardness can be obtained. On the other hand, when the C content is higher than 0.50 mass %, microsegregation is promoted to reduce toughness, or the amount of solid solution carbon increases to reduce the thermal conductivity of the additively manufactured body. Therefore, the C content is 0.30 mass % or more and 0.50 mass % or less, preferably 0.35 mass % or more and 0.45 mass % or less.
[0069] (Si content)
[0070] Si is an essential element that improves hardness by solid solution in the matrix. In addition, Si has the effect of improving softening resistance. When the content of Si is higher than 0.40 mass%, Si does not form carbides but is integrated into the matrix, thereby greatly reducing the thermal conductivity of the additively manufactured body. Therefore, the content of Si is less than 0.40 mass%, preferably less than 0.35 mass%. The lower limit of the content of Si is not particularly limited as long as it is higher than 0 mass%, but is preferably 0.05 mass% or more, more preferably 0.10 mass% or more.
[0071] (Mn content)
[0072] Mn is an essential element that improves hardenability and suppresses the reduction of toughness caused by bainite formation. In addition, Mn has the effect of improving softening resistance. When the content of Mn is higher than 0.40 mass %, Mn is dissolved in the matrix and the thermal conductivity of the additively manufactured body is reduced. Therefore, the content of Mn is less than 0.40 mass %, preferably less than 0.35 mass %. The lower limit of the content of Mn is not particularly limited as long as it is higher than 0 mass %, but is preferably more than 0.15 mass %, more preferably more than 0.20 mass %.
[0073] (Cr content)
[0074] Cr is an essential element for improving hardenability and suppressing the reduction of toughness due to bainite formation. In addition, Cr has the effect of improving softening resistance. When the Cr content is less than 0.85 mass %, the Ms point becomes too high, and when the Cr content is higher than 1.75 mass %, the Ms point becomes too low. Therefore, in order to make the Ms point within the appropriate temperature range, the Cr content is 0.85 mass % or more and 1.75 mass % or less, preferably 0.90 mass % or more and 1.50 mass %, more preferably 0.90 mass % or more and 1.20 mass % or less.
[0075] (Ni content)
[0076] Ni is an essential element for improving hardenability and suppressing the reduction in toughness caused by bainite formation. In addition, since Ni does not form carbides and melts into the matrix, the thermal conductivity of the additively manufactured body is reduced. When the content of Ni is higher than 0.40% by mass, the thermal conductivity of the additively manufactured body is greatly reduced. Therefore, the content of Ni is less than 0.40% by mass, preferably less than 0.30% by mass. The lower limit of the content of Ni is not particularly limited as long as it is higher than 0% by mass, but is preferably more than 0.10% by mass, and more preferably more than 0.20% by mass.
[0077] (Mo content)
[0078] Mo is an essential element that promotes secondary hardening during tempering and improves quenching and tempering hardness. In addition, even if Mo is added, the contribution to the reduction of thermal conductivity of the additively manufactured body is also small, and the effect of improving the hardness of the additively manufactured body is large. Therefore, the content of Mo is more than 0.70 mass %. On the other hand, when the content of Mo is higher than 1.20 mass %, the amount of Mo remaining in the matrix increases, which easily reduces the thermal conductivity of the additively manufactured body. Therefore, the content of Mo is less than 1.20 mass %. That is, the content of Mo is more than 0.70 mass % and less than 1.20 mass %, preferably more than 0.75 mass % and less than 1.00 mass %.
[0079] (V content)
[0080] V is an essential element for promoting secondary hardening during tempering and improving quenching and tempering hardness. However, when the content of V is higher than 0.60% by mass, the amount of V remaining in the matrix increases, which reduces the thermal conductivity of the additively manufactured body. Therefore, the content of V is less than 0.60% by mass, preferably less than 0.50% by mass. The lower limit of the content of V is not particularly limited as long as it is higher than 0% by mass, but is preferably more than 0.20% by mass, more preferably more than 0.30% by mass.
[0081] (Al content)
[0082] Al is an essential element for forming nitrides and inhibiting grain coarsening during quenching. However, when the content of Al is higher than 0.10% by mass, Al nitrides are easily formed excessively, which reduces the toughness of the additively manufactured body. Therefore, the content of Al is less than 0.10% by mass, preferably less than 0.06% by mass. The lower limit of the content of Al is not particularly limited as long as it is higher than 0% by mass, but is preferably 0.01% by mass or more, and more preferably 0.02% by mass or more.
[0083] (W content)
[0084] W is an arbitrary element that promotes secondary hardening during tempering and improves quenching and tempering hardness. However, when the content of W is higher than 0.40 mass %, the amount of W remaining in the matrix increases, and the thermal conductivity of the additively manufactured body is easily reduced. Therefore, the content of W is less than 0.40 mass %, preferably less than 0.30 mass %. The lower limit of the content of W is 0 mass %, but if W is contained, it is preferably more than 0.10 mass %, more preferably more than 0.20 mass %.
[0085] (Indicator K1)
[0086] The index K1 is an index (mass %) for evaluating the quenching and tempering hardness, and is represented by the following formula (13).
[0087] [Formula 4]
[0088]
[0089] C, Si, Mo and W shown in the above formula (13) represent the content (mass %) of each element in the Fe-based alloy powder. By measuring the content of each element, the index K1 can be calculated. The larger the index K1, the greater the tempering hardness. In order to improve the index K1, it is effective to add elements such as C, Si, Mo and W, and it is particularly effective to add C and Mo. By adjusting the contents of C, Si, Mo and W so that the index K1 reaches 17.00 mass % or more, the quenching and tempering hardness can be made 42.0HRC or more in the additive manufacturing body manufactured using the Fe-based alloy powder. As described later, in order to ensure the life of the additive manufacturing body, the quenching and tempering hardness is preferably 42.0HRC or more. The preferred index K1 is 18.0 mass % or more. The upper limit value of the index K1 is not particularly limited, but is usually 25.0 mass % or less, and more typically 21.0 mass % or less.
[0090] (Indicator K2)
[0091] The index K2 is an index for evaluating thermal conductivity (mass %) and is represented by the following formula (14).
[0092] [Formula 5]
[0093]
[0094] C, Si, Mn, Cr, Ni, Mo, W, V and Al shown in the above formula (14) represent the content (mass %) of each element in the Fe-based alloy powder. By measuring the content of each element, the index K2 can be calculated. When the index K2 is less than 44.00 mass %, the amount of alloy elements remaining in the matrix increases, and the thermal conductivity is easily reduced. Therefore, the index K2 is preferably greater than 44.00 mass %. More preferably, the index K2 is greater than 46.0 mass %. The upper limit value of the index K2 is not particularly limited, but is usually less than 50.0 mass %, and more typically less than 48.0 mass %.
[0095] (Average particle size D 50 )
[0096] In order to make the Fe-based alloy powder easy to lay when manufacturing additively manufactured products, the fluidity of the Fe-based alloy powder is required. Considering this point, the average particle size D of the Fe-based alloy powder is preferably 50 On the other hand, if the particle size of the Fe-based alloy powder is too small, the Fe-based alloy powder is difficult to handle, so the average particle size D of the Fe-based alloy powder is 50 It is preferably 20 μm or more.
[0097] Average particle size D 50 The mean particle size D is the particle size at which the cumulative volume is 50% in the cumulative distribution when the total volume of the Fe-based alloy powder is 100% (also called the median particle size). The particle size of the Fe-based alloy powder can be measured using a laser diffraction scattering method or the like, and a suitable method for measuring the mean particle size D is 50 An example of a laser diffraction scattering particle size distribution measuring device is Microtrac MT3000 from Nikkiso Co., Ltd. Fe-based alloy powder and pure water are poured into the sample cell of the measuring device, and the particle size of the Fe-based alloy powder can be measured based on the light scattering information of the Fe-based alloy powder.
[0098] (Thermal conductivity of additively manufactured bodies)
[0099] When an additively manufactured body made of Fe-based alloy powder is used as a hot die for hot stamping or die casting, in order to improve the cooling efficiency of the additively manufactured body, the thermal conductivity (room temperature) of the additively manufactured body after tempering is preferably 40.0 W / m·K or more. In addition, the thermal conductivity (room temperature) is more preferably 42.0 W / m·K or more.
[0100] (Hardness of additively manufactured bodies)
[0101] When using an additively manufactured body made of Fe-based alloy powder as a hot die for hot stamping or die casting, in order to obtain a sufficient life, the hardness of the additively manufactured body after quenching and tempering is preferably 42.0 HRC or more. This hardness can be measured by following the Rockwell hardness test specified in JIS Z2245.
[0102] Example
[0103] Examples 1 to 12 and Comparative Examples 1 to 7
[0104] In each example, raw materials having the chemical composition shown in Table 1 were used. Fe-based alloy powders were produced from each raw material using a gas atomization method. Table 1 shows, in addition to the chemical composition, the indexes K1, K2, carbon equivalent Ceq, Ms point, and average particle size D 50 In Table 1 below, values that do not satisfy the conditions shown in the above formulas (1) to (10) are underlined.
[0105]
Table 1
[0106]
[0107] In the production of Fe-based alloy powder, each raw material is heated (high-frequency induction heating) in a crucible made of alumina in a vacuum to form a molten alloy, and then the molten alloy is dropped from a nozzle with a diameter of 5 mm set at the bottom of the crucible. By spraying high-pressure argon gas on the molten metal, the molten alloy is finely divided and rapidly cooled to obtain a large amount of fine powder. The obtained powder is sieved to obtain Fe-based alloy powder with a particle size of less than 63μm.
[0108] A rectangular additive manufacturing body (test piece) of 15 mm in length × 100 mm in width × 15 mm in height was manufactured from the Fe-based alloy powder obtained in each example using a three-dimensional additive manufacturing device (EOS-M280; EOS (Electro Optical Systems) Co., Ltd.). The standard parameters of the device (MS1, layer thickness 40 μm) were used for the laser irradiation conditions during the molding.
[0109] (Tempering)
[0110] Each additively manufactured body was tempered. Specifically, each additively manufactured body was kept at 600°C for 60 minutes and then air-cooled twice. In addition, in the three-dimensional additive manufacturing method, since quenching is performed by rapid cooling during molding, only tempering was performed without quenching.
[0111] (Measurement of tempering hardness)
[0112] The hardness (HRC) of the surface perpendicular to the stacking direction of the additively manufactured body subjected to the above-mentioned tempering was measured using a Rockwell hardness tester. The measurement results are shown in Table 2. In Table 2, values with tempered hardness lower than 42.0 HRC are underlined.
[0113] (Measurement of thermal conductivity)
[0114] After the tempered additively manufactured body was finished into a disk shape with a diameter of 10 mm and a thickness of 1 mm, the thermal conductivity of each additively manufactured body was measured by using a laser flash method. The measurement results are shown in Table 2. In Table 2, the values with a thermal conductivity lower than 40.0 W / m·K are underlined.
[0115] (Crack determination)
[0116] Each additively manufactured body (a rectangular parallelepiped with a length of 15 mm × a width of 100 mm × a height of 15 mm) was visually checked to determine whether there was a crack. Specifically, when a crack occurred on at least one face of the additively manufactured body (rectangular parallelepiped), it was determined to be cracked, and when a crack did not occur on any face of the additively manufactured body (rectangular parallelepiped), it was determined to be crack-free. The results of the determination are shown in Table 2. In the crack determination shown in Table 2 below, "○" indicates no crack, and "×" indicates crack.
[0117]
Table 2
[0118]
[0119] In Examples 1 to 12, the content of each element contained in the Fe-based alloy powder is within the numerical range shown in the above formulas (1) to (8), and in the Fe-based alloy powder containing W (Examples 1 and 3 to 12), the content of W is 0.40 mass % or less. In addition, in Examples 1 to 12, the carbon equivalent Ceq satisfies the condition shown in the above formula (9). As a result, in the additively manufactured body manufactured using the Fe-based alloy powder of Examples 1 to 12, the occurrence of cracks can be suppressed. In addition, in Examples 1 to 12, the Ms point also satisfies the condition shown in the above formula (10).
[0120] In addition, regarding the tempering hardness of the additively manufactured body, it is possible to ensure a tempering hardness of 42.0 HRC or more, and regarding the thermal conductivity of the additively manufactured body, it is possible to maintain a thermal conductivity of 40.0 W / m·K or more. By making the tempering hardness of the additively manufactured body 42.0 HRC or more, it is easy to increase the life of the additively manufactured body. In addition, by making the thermal conductivity of the additively manufactured body 40.0 W / m·K or more, it is easy to improve the cooling efficiency of the additively manufactured body.
[0121] In Comparative Examples 2, 4, and 6, the carbon equivalent Ceq does not satisfy the condition shown in the above formula (9), and in Comparative Examples 1, 3, 5, and 6, the Ms point does not satisfy the condition shown in the above formula (10). In addition, in Comparative Example 7, the Cr content does not satisfy the condition shown in the above formula (4). As a result, cracks occurred in the additively manufactured bodies made from the Fe-based alloy powders of Comparative Examples 1 to 7. On the other hand, in Comparative Examples 3 and 5, the tempering hardness of the additively manufactured bodies was lower than 42.0HRC, and sufficient hardness could not be ensured. In Comparative Example 6, the thermal conductivity of the additively manufactured body was lower than 40.0W / m·K, and sufficient thermal conductivity could not be ensured.
Claims
1. An Fe-based alloy powder, wherein: In terms of mass%, it contains: 0.30≤C≤0.50、 0<Si≤0.40、 0<Mn≤0.40、 0.85≤Cr≤1.75、 0<Ni≤0.40、 0.70≤Mo≤1.20, 0<V≤0.60、 0<Al≤0.10、 0≤W≤0.40%, The balance contains Fe and unavoidable impurities, Among the elements contained in the Fe-based alloy powder, a carbon equivalent Ceq obtained by converting the influence of elements other than carbon into a carbon amount is 0.95 mass % or less.
2. The Fe-based alloy powder according to claim 1, wherein It has an Ms point of 340°C to 385°C.
3. The Fe-based alloy powder according to claim 1, wherein W is contained in an amount exceeding 0 mass % and not more than 0.40 mass %.
4. The Fe-based alloy powder according to any one of claims 1 to 3, wherein The index K1 represented by the following formula is 17.00 mass % or more, Furthermore, the index K2 represented by the following formula is 44.00 mass % or more, 。 5. A method for manufacturing an additively manufactured body, wherein: include: An additively manufactured product is manufactured by irradiating an Fe-based alloy powder according to any one of claims 1 to 3 with an energy beam to melt and solidify the powder.
Citation Information
Patent Citations
Metal powder
JP2021181591A
Shaped body formed from powder
JP2022092524A